HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL SMASH BOLA VOLI PADA ATLET PUTRA SMA NEGERI 2 KUOK - Arif, Ahmad; Slamet, Slamet; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on observations made by the reseacher in the field, and also based on information from the trainers (teachers) and athletes, that men's volleyball sports at SMA Negeri 2 Kuok have not been able to show maximum achievement. One of the causes of this is a smash, such as a ball stuck on the net, a ball can be returned or blocked by an opponent, the ball is not on target or the ball is out of the playing field. The purpose of this research was to prove the correlation between leg muscle strength and the flexibility of the back muscles with the smash results in male volleyball athletes at SMA 2 Kuok. The population in this research were all male volleyball athletes from SMA 2 Kuok who participated in volleyball exercises totaling 12. The sampling used total sampling so that the sample in this research was 12 people. The instruments in this research were leg dynamometer, sit and reach and volleyball smash results. The data obtained are analyzed using product moment correlation. Based on the results of the research that the researcher has described in the previous chapter, it can be concluded that the results obtained from leg muscle strength have no correlation with the results of Smash in volleyball athletes. From the results obtained the flexibility of the back muscles has no correlation with the results of Smash in volleyball athletes. There is no joint relationship between leg muscle strength and the flexibility of the back muscle the results of Smash in volleyball athletes.Key Words: Leg Muscle Strength, Back Muscle Detection, Smash Results